Penerapan e-book berbasis socio-scientific issues dalam meningkatkan kemandirian belajar pada materi sistem sirkulasi darah - Reza Kharisma Siswi Laksono; Heru Nurcahyo; Yuni Wibowo (JINoP (Jurnal Inovasi Pembelajaran), 2023)
Independent learning is an important aspect for students to learn without being accompanied by a teacher (learning outside the classroom). The purpose of this study was to determine the effectiveness of e-books based on socio-scientific issues (SSI) in increasing students’ learning independence on the material of the blood circulation system. The research method used is a quantitative method, with a nonequivalent control group design. The sample in this study were two class XI in one high school in Yogyakarta, each class amounted to 33 students. The instrument used is a learning independence questionnaire, with reference to 5 aspects of learning independence. Hypothesis testing was carried out with the help of SPSS using the Mann Whitney U test. In addition, data analysis techniques were also carried out using the n-gain score. The results of hypothesis testing regarding learning independence using the Mann-Whittney U test showed that there was a significant difference in the average value of learning independence between the experimental class and the control class. Then, the average gain score for students’ learning independence in the experimental class was 0.64 which was included in the medium category. While the average in the control class is 0.27 in the low category. It can be concluded that the use of SSI-based e-book media is effective in increasing students’ learning independence on the material of the blood circulation system.